Attitudes regarding becoming an engaged bystander for targeted violence prevention - Gleicher, Lily (Crime prevention and community safety, 2020)
The recent increase in mass attacks in the USA has enhanced concerns about how persons in communities might be able to contribute to the prevention of such incidents and other forms of targeted violence. The purpose of this study was to learn about what persons are willing to do regarding individuals exhibiting or vocalizing concerning behaviors, and what factors would impact their actions. This was accomplished through 9 focus groups of 72 persons total, in which participants were asked to provide their perceptions regarding six different behavior-based scenarios involving acquaintances, close friends or family members. The study found that participants were willing to engage someone in a conversation, take some type of action with friends and family, contact law enforcement if there is imminent danger, and use a third-party resource when the behavior viewed was particularly concerning. Implications of these findings for targeted violence prevention efforts are discussed.